The effectiveness of dumbbell training on improving overhand serve ability in volleyball: an experimental study on beginner athletes - Arga, Mochhammad Imam Bastomi; Sudjandoko, Andun; Yuliastrid, Dita; Nugroho, Testa Adi (Sriwijaya Journal of Sport, 2026)
Research Background: Beginner volleyball athletes often experience difficulties in performing effective overhead serves, particularly in terms of strength and accuracy. One of the contributing factors is the lack of appropriate training methods that specifically target upper limb strength. Therefore, it is necessary to examine whether variations in dumbbell load (500 grams and 600 grams) can significantly improve overhead serve ability. Research Objective: This study aimed to examine the effect of different dumbbell loads, namely 500 grams and 600 grams, on improving volleyball overhead serve ability among beginner athletes. Method: This study employed an experimental design using a pretest-posttest control group design. The participants were 30 beginner athletes from the Bintang Muda Kediri Club. The samples were divided into three groups using the ordinal pairing technique: a 500-gram dumbbell group, a 600-gram dumbbell group, and a control group. The training program was conducted over four weeks, with a frequency of three sessions per week. Data were analyzed using ANOVA to determine differences between groups. Results: The results indicated a significant improvement in overhead serve ability across all groups (p < 0.05). However, the group trained with 600-gram dumbbells showed the highest improvement compared to the other groups. The ANOVA test results (F = 44.23; p = 0.000) confirmed that there were significant differences among the groups. Conclusion: Both 500-gram and 600-gram dumbbell training were effective in improving overhead serve ability among beginner volleyball athletes. However, the 600-gram dumbbell load was found to be more effective. These findings suggest that incorporating appropriate resistance training can provide practical benefits for coaches in designing structured training programs to enhance athletes’ performance.